Financial integration and international shock transmission: The terms-of-trade effect - Johanna Krenz (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2023)
What are the effects of financial integration on global comovement? Using a standard two-country DSGE model, I show that in response to country-specific supply shocks higher exposure to foreign assets leads to lower cross-country output correlations, while the opposite is true for country-specific demand shocks. I argue that an important, yet overlooked, transmission channel originates in the interplay between financial integration and terms of trade movements in response to the shocks hitting the economy. The transmission channel is independent of whether the agents who hold the foreign assets are financially constrained or not.
Keywords: E30; E44; F41; F44; G15; 330; Business cycle comovement; Financial cycle comovement; Financial integration; Demand versus supply shocks; Terms of trade; Transfer Problem; Balance sheet effect